1696. Comparison of in vitro activities of linezolid and contezolid against clinical Nocardia isolates. (15th December 2022) - Wei, Ming; Wang, Peng; Wang, Shuai; Yang, Chunxia; Degree, Master's; Gu, Li
Abstract: Background: Nocardia is nearly 100% susceptible to linezolid which is one of the first-line agents for all clinical species and isolates reported in the literature. However, adverse reactions related to myelosuppression and monoamine oxidase inhibition have limited linezolid use to some extent. Contezolid, a new oxazolidinone antibiotic that has decreased toxicity compared to linezolid, was launched in China in June 2021. In this study, the in vitro activities of linezolid and contezolid are compared against Nocardia . Methods: Ninety-four clinical Nocardia isolates from Beijing Chao-Yang Hospital were identified by multilocus sequence analysis, and the in vitro activities of linezolid and contezolid were evaluated using the broth microdilution method. A Wilcoxon Signed Rank Test was performed to determine if linezolid and contezolid are significantly different from each other against clinical Nocardia isolates. Results: Pulmonary nocardiosis (91.5%) was the most common clinical presentation of Nocardia infections. N. cyriacigeorgica (36.2%) and N. farcinica (16.0%) were the most frequently encountered Nocardia species, followed by N. abscessus (9.6%) and N. otitidiscaviarum (9.6%). The MIC (minimum inhibitory concentration) ranges of all clinical Nocardia isolates for linezolid and contezolid were 0.5-8 μg/mL. The MIC50 /MIC90 values for all isolates of Nocardia for linezolid vs contezolid was 2/4 μg/mL vs 2/4 μg/mL, and for N. cyriacigeorgica and N. farcinica were 4/4 μg/mL vs 2/4 μg/mL and 4/4μg/mL vs 2/4 μg/mL, respectively. After a Wilcoxon Signed Rank Test analysis, the P values of all Nocardia isolates was < 0.001, and for N. cyriacigeorgica and N. farcinica were 0.001 and 0.020, respectively. Conclusion: Though MIC50 /MIC90 values for linezolid and contezolid for all Nocardia isolates evaluated appeared to be similar, there was a statistically significant difference between the two antibiotics. Furthermore, the MIC50 values for the most commonly encountered species N. cyriacigeorgica and N. farcinica were lower for contezolid than for linezolid. Therefore, the in vitro activity of contezolid is better than that of linezolid against clinical Nocardia isolates, and contezolid could also be an option for the treatment of Nocardia infections. Disclosures: All Authors : No reported disclosures.